Resource Areas and Particle Size Analyses of Desert Dusts that Influence East and South-East Anatolian Regions - Sengun, Taner; Kiransan, Kemal (Istanbul Univ, Fac Letters, Dept Geography, 2012)
Desert dusts occur by the transportation of dusts in soil into atmosphere and then by the longdistance atmospheric transportation of these dust particles relying upon climate factors in inland regions and subtropical desert regions away from costs. East and South-East Anatolian regions began to get affected due to the dusts originating from deserts in the recent years. Many sources of information such as the data provided by the Turkish State Meteorology Office, desert dust concentration maps, and desert dust specimens obtained by field works and observations have been utilized to understand the root cause of this situation. The diffusion areas of dusts with respect to the dust concentration maps have been followed up daily, taking necessary pictures and specimens. According to the results of studies, the majority of desert dusts is carried away into East and South-East Anatolia from the Sahara desert, the deserts of Arabian Peninsula, and Persian deserts. The geographical features, climate, and the morphological factors were influential on the creation of this situation. Syrian and Iraqi deserts transport more dust into East and South-East Anatolian regions than the Sahara desert due to the fact that they are situated in a closer location and that they are on the direction of dynamic depression movements. The effects of desert the dusts originating from Persian deserts upon East and South-East Anatolian regions are very weak compared to those of the Sahara desert and the deserts of Arabian Peninsula. The dusts airborne due to severe winds in the Turkish mainland would also fly away into other regions. This is a small amount though. In the study, the particle size analyses and the resource regions of desert dusts affecting East and South-East of Anatolia were generally investigated.
Keywords: Desert dust; East and South-East Anatolian regions; The Sahara desert; Dust transportation; The deserts of Arabian Peninsula